Kinetic properties of raffinose synthase from rice (Oryza sativa L.). (October 2018) - Li, Tuoping; Dong, Mosi; Xie, Wanying; Zhang, Yifan; Tao, Dongbing; Li, Suhong
Abstract: The kinetic properties of purified recombinant rice raffinose synthase (RS) suggested the catalytic mechanisms for RS for both hydrolysis and synthesis reactions. The hydrolysis K m values of rice RS were found to be 2.15, 10.9 and 12.0 mM for galactinol, raffinose, and p -nitrophenyl-α-d -galactopyranoside, respectively. In synthesis reactions, the enzyme transferred galactose from galactinol to sucrose to yield raffinose and myo -inostiol. The raffinose synthesis was best fitted to a Ping-Pong Bi-Bi mechanism, with K m values of 6.7 and 18.5 mM estimated at non-saturated substrate levels for galactinol and sucrose. The synthesis, catalyzed by rice RS was reversible, the forward reactions approached equilibrium after 4 h, and the K eq was calculated to be 4.46. The specific activity 25.6 nkat/mg for raffinose formation was more efficient than that of other RS.